Penetapan Harga Jasa Pendidikan di Perguruan Tinggi Keagamaan Islam Negeri (PTKIN) - Mukhlison Effendi; Nur Aini Latifah (LP. Ma'arif Janggan Magetan, 2021)
Pricing is a critical decision that supports the successful operation of profit and non-profit organizations. Price is the only element of the marketing mix that generates revenue for the organization. However, decisions regarding prices are not easy to make. All for-profit organizations and many non-profit organizations charge prices for their products or services. This study aims to determine the amount of single tuition fee (UKT) that is applied at State Universities in Indonesia. With the literature study method, it can be explained that the determination of the single tuition fee is a policy aimed at helping and reducing the cost of student education. No other additional fees will be charged for 8 semesters. The determination of a single tuition fee also makes it easy to predict student tuition expenses each semester. The size of the costs incurred also follow the size of the needs such as the cost of practicum in each study program